Fundamentals of library supervision - McNeil, Beth (Neal-Schuman, an imprint of the American Library Association, 2017)
Today's workplace includes a wider generational range of staff, and is governed by more complex legal issues. Poor supervisory skills can compound morale problems and lead to organizational issues. McNeil covers the fundamentals of good supervision and management, while providing practical advice with basic commonsense approaches to solving today's management challenges.